Why parents are skeptical about using probiotics preventively for small children: a Danish qualitative study - S. S. Andersen; K. F. Michaelsen; R. P. Laursen; L. Holm (BMC, 2018)
Abstract Background Research on the health effects of probiotics continues to grow, but less is known about consumers' perceptions of probiotic products and their health effects, and the impact of these perceptions on consumption. Particularly little is known about the way parents perceive probiotic consumption by small children, and whether parental willingness to use probiotics as a treatment differs from their willingness to use them preventively. The aim of this study was to explore how parents perceive probiotic consumption by their small children, and their willingness to use such products in treatment and prevention. Methods Semi-structured qualitative interviews with 17 Danish parents with at least one child aged 8-18 months. The interview guide centered on parental consumer practices and health-related attitudes both in general and in relation to probiotics. The data were coded in Nvivo and analyzed in a four-step analytical approach. Results Parents are willing to use probiotics as a treatment but are skeptical about preventive use. Some parents define probiotics as a kind of medicine they use only if their child is ill. Probiotics also conflict with parental understandings of their children as small, perfect parts of nature. Parents worry that probiotics may cause an imbalance in the vulnerable perfection of a small child. Conclusion The study shows that parental probiotic consumption practices are embedded in a cultural understanding of the child as both a perfect example of nature and vulnerable. Health authorities need to take this understanding into account if parents are to be successfully encouraged to use probiotics preventively.